Instantaneous Frequency Extraction Using the EMD-Based Wavelet Ridge to Reveal Geological Features - Xue, Ya-juan; Zhang, Jian; Chang, Qiang; Zhang, Li-ping; Zou, Feng (Frontiers in Earth Science, 2018)
As one of the important seismic attributes, instantaneous frequency is widely used to reveal geological features. Compared to the normally instantaneous frequency extraction using Hilbert transform (HT), instantaneous frequency extraction using the wavelet ridge is demonstrated to have a more robust characteristic and anti-noise feature. Due to instantaneous frequency extraction using the wavelet ridge is suitable for the gradual single-frequency signal, to get a meaningful instantaneous attributes Empirical Mode Decomposition (EMD) is applied to the seismic signal first to decompose each seismic trace into the IMFs which are single-frequency signal. Application of the simulated signals and the seismic trace show that instantaneous frequency extraction using the EMD-based wavelet ridge is more accurate than HT does. Application of the EMD-based wavelet ridge method in a gas field located in PengLai, Central Sichuan(China), shows its effectiveness. Instantaneous frequency extraction using the EMD-based wavelet ridge method can be used as a strong tool to detect the instantaneous spectral properties of a reservoir to reveal hydrocarbon related strong amplitude anomaly and reservoir thickness variation and lateral changes information.